Children with cancer : a reference guide for parents - Bracken, Jeanne Munn (Oxford University Press, 2010)
"Children with Cancer draws together a wealth of up-to-date information essential for anyone who wishes to help a child or family through this ordeal--including relatives, friends, teachers, and clergymen, as well as doctors, nurses, and other health care professionals"--Provided by publisher